Meaning-Centered Psychotherapy for Latino Patients with Advanced Cancer: Cultural Adaptation Process - Costas-Muñiz, Rosario (J Palliat Med, 2020)
Background: Latino patients with advanced cancer need culturally responsive, effective psychotherapeutic interventions that can assist them in coping with their diagnosis and improve spiritual and existential well-being and psychological adjustment. Objective: This study describes the cultural and linguistic adaptation of individual meaning-centered psychotherapy for Latinos with advanced cancer. Design: A mixed-methods, concurrent integrative approach was used for this study, using the ecological validity and cultural adaptation process models as frameworks for cultural adaptation. Setting/Subjects and Measurements: Quantitative and qualitative data were collected through (1) a survey of mental health professionals (n = 70) who offer services to Latino cancer patients; (2) a questionnaire for Latino patients with advanced cancer (n = 54), measuring relevant intervention concepts; and (3) in-depth interviews with 24 Latino patients. Results: Quantitative findings showed that most of the goals and concepts were highly acceptable for patients and providers. The qualitative findings supported adaptations to include using more simple definitions; changing phrases that are challenging to translate and comprehend; using words that are common to all Latino cultures, providing more than one option if needed; simplifying the questions/reflections, as needed; changing the metaphors to be culturally congruent; and modifying content to make it responsive to Latino cultural values and norms. Conclusions: Findings demonstrate the need for adaptation to achieve the aims of the intervention, accounting for both linguistic and cultural considerations, emphasizing issues related to literacy, cultural and linguistic diversity, cultural values, and culturally congruent content. The mixed-methods approach is described to provide recommendations for clinicians, researchers, and program developers.